Spectrophotometric Determination of Tolterodine Tartarate and Repaglinide - GOWRI SANKAR, D.; DURVASA RAO, B.; MADHAVI LATHA, P.V.; VAMSI KRISHNA, M. (Asian Journal of Chemistry, 2010)
Simple and sensitive spectrophotometric methods has been developed for the estimation of tolterodine tartarate and repaglinide in pure as well as in pharmaceutical formulations. These methods are based on the oxidation of drug with ferric chloride followed by complexation with 2,2-bipyridyl to form a blood red colored chromogen, exhibiting maxiumum absorbance at 530 nm and obeyed Beer’s law in the concentration range of 5-20 μg/mL. These methods were extended to pharmaceutical formulations. There was no interference from any common pharmaceutical excepients and diluents.